Peran Wali Pemasyarakatan Dalam Meningkatkan Self Esteem Warga Binaan Kelas II A Kupang - Melkianus Mone Mangngi; Ezra Tari; Nelman A. Weny (CV. Ulil Albab Corp, 2022)
Indonesia is a country of law which aims to maintain and create security and order in the community. But what happened was that there were still many social problems that occurred so that they became entangled with the law and eventually ended up in prison as fostered citizens. When becoming a fostered citizen, it will have an impact on the passion of oneself and for others or in short that the decline of self-esteem. This condition requires assistance so that it can increase the self-esteem of the assisted residents and the one who plays a role in this situation is the Correctional Guardian. The purpose of this study is to describe and analyze the role of Correctional Guardian assistance, forms of assistance and relevant methods in increasing the self-esteem of assisted residents. This type of research is qualitative research, a phenomonological approach. The results of the study found that there was an increase in self-esteem from the assisted residents after assistance was carried out by the Correctional Guardian. The forms of mentoring carried out are personality coaching including spiritual coaching, health and education and independence coaching in the form of interests and talents or skills. The relevant methods used in mentoring are involving assisted residents in the work of the Correctional Guardian, designing work programs and being entrusted with leadership. Then make clothes with constructive writing, make pictures and posters that direct the eyes of the fostered citizens in a direction that builds, restores and is motivated.